Extreme stratospheric springs and their consequences for the onset of polar mesospheric clouds. (September 2015) - Siskind, David E.; Allen, Douglas R.; Randall, Cora E.; Harvey, V. Lynn; Hervig, Mark E.; Lumpe, Jerry; Thurairajah, Brentha; Bailey, Scott M.; Russell, James M.
Abstract: We use data from the Aeronomy of Ice in the Mesosphere (AIM) explorer and from the NASA Modern Era Retrospective Analysis for Research and Applications (MERRA) stratospheric analysis to explore the variability in the onset of the Northern Hemisphere (NH) Polar Mesospheric Cloud (PMC) season. Consistent with recently published results, we show that the early onset of the NH PMC season in 2013 was accompanied by a warm springtime stratosphere; conversely, we show that the late onset in 2008 coincides with a very cold springtime stratosphere. Similar stratospheric temperature anomalies for 1997 and 2011 also are connected either directly, through observed temperatures, or indirectly, through an early PMC onset, to conditions near the mesopause. These 4 years, 2008, 1997, 2011, and 2013 represent the extremes of stratospheric springtime temperatures seen in the MERRA analysis and correspond to analogous extrema in planetary wave activity. The three years with enhanced planetary wave activity (1997, 2011 and 2013) are shown to coincide with the recently identified stratospheric Frozen In Anticyclone (FrIAC) phenomenon. FrIACs in 1997 and 2013 are associated with early PMC onsets; however, the dramatic FrIAC of 2011 is not. This may be because the 2011 FrIAC occurred too early in the spring. The link between NH PMC onset and stratospheric FrIAC occurrences represents a new mode of coupling between the stratosphere and mesosphere. Since FrIACs appear to be more frequent in recent years, we speculate that as a result, PMCs may occur earlier as well. Finally we compare the zonal mean zonal winds and observed gravity wave activity for the FrIACs of 2011 and 2013. We find no evidence that gravity wave activity was favored in 2013 relative to 2011, thus suggesting that direct forcing by planetary waves was the key mechanism in accelerating the cooling and moistening of the NH mesopause region in May of 2013. Highlights: The variation in onset dates for the PMC seasons is studied. Extremes in onset correspond to stratospheric planetary wave variability. Stratospheric frozen in anticyclones can serve as proxy for early PMC onset. Gravity wave activity not enhanced for the 2013 early PMC onset.